Educating the English: the role of universities in tackling hate speech and Islamaphobia in post-EU-Referendum Britain - Evenden-Kenyon, Elizabeth (Papeles de Europa, 2020)
This essay will examine the role of the Higher Education system in the UK, in educating students and communities about the concept of ‘othering’, and how they can combat ignorance of the benefits of multiculturalism and Freedom of Movement. Since the Referendum over membership of the EU (June 2016), hate crime and speech has soared in the UK – verbally and on social media – as have physical attacks on migrants and ethnic minorities. Recent research suggests that this increase has been fuelled by the language and images used in certain UK media. This essay will therefore consider the impact of media ‘othering’ and what universities can, are, and might do to combat this rhetoric and action. It will consider current practices, policies, and posit future paths for Higher Education and governmental Education policy, in tackling xenophobia and Islamaphobia within the UK.